Le capital - Marx, Karl; Roy, M.J. (Paris : Librairie du Progrès, 1875)
Fonds perrone
Fotokopieën van de eerste druk. Origineel wordt bewaard in kluis
Bevat annotaties
Frans
Monografie
Keywords: marxistische economie